Identifikasi Karakteristik dan Faktor Pengaruh pada Berbagai Tipe Longsor - Pranatasari Dyah Susanti; Arina Miardini (agriTECH, 2019)
Landslide disaster mitigation is necessary in areas vulnerable to this disaster. Banjarnegara is one of the regencies in Central Java Province with high ground movement potential, hence, it is prone to landslides. The aim of this study was to determine the characteristics and factors that influence the type of landslides in Banjarnegara District. The observation of the research was based on the results of landslide vulnerability analysis. Identification of the landslides characteristics, both in types and factors that influence them, are carried out by a survey method with a purposive random sampling technique by considering the locations that have experienced landslides, and the level of vulnerability to landslides. The survey was conducted using a landslide control card (KKL) which was compiled based on the factors that cause landslides. Scoring was done to determine the determinants of the landslide type quantitatively, on a scale of 1 to 5. The results showed that there were three types of landslides found in the study location, namely rotational slide, creep slide and flows. Factors that influenced rotational slide in the study site were slope, soil depth, faults, and infrastructure, while for creep slide were faults, slope, length of slope, and infrastructure. In addition, flows were affected by faults and infrastructure. The highest KKL value was 77 in the rotation landslide type and the lowest was 51 in the creep landslide type. Rainfall is also a trigger factor for the three types of landslides. It is highly recommended to do technical mitigation by observing the principles of soil and water conservation and high adaptation to the people living in this area.